The Effectiveness of the Electronic Traffic Law Enforcement (ETLE) Programme in Increasing Public Compliance in Medan City (Case Study of the Traffic Directorate of the North Sumatra Regional Police) - Saibi, Karina Farsha; Sihombing, Sally Marisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyse the Effectiveness of the Electronic Traffic Law Enforcement (ETLE) Program in improving public compliance in Medan City using qualitative research methods. Data collection was carried out using interview, observation and documentation techniques. Data was obtained through primary and secondary data and analysed using data reduction, data presentation, and conclusion drawing. The results of this study indicate that the effectiveness of the Electronic Traffic Law Enforcement (ETLE) program in improving community compliance in Medan City is already running but there is still a need for massive socialisation and also accelerating the process of connecting static ETLE at several points that have not been directly connected to the back office dashboard so that enforcement has not been carried out optimally so that the objectives of the ETLE program, namely Kamseltibcarlantas (Security, Safety, Order and smoothness of Traffic) can be carried out properly.